CONVERSION OF PRODUCTIVE AGRICULTURAL LAND WITH ANALYSIS OF GEOGRAPHICAL INFORMATION SYSTEMS IN DIBAL VILLAGE, 2010-2020 - Zuhdiyah Matienatul Iemaaniah; Rika Andriyani Sukma Dewi; Latifah Nurul Qomariyatuzzamzami; Muhammad Zaki Zamani (Universitas Sebelas Maret (UNS), 2023)
Land conversion will continue to occur over time. Population growth and regional development can cause land conversion. It is undeniable that land conversion will change vacant land, especially productive agricultural land, into built-up land. The purpose of this study is to determine the extent of changes in productive agricultural land and the conversion of productive agricultural land. Within 10 years Dibal Village has experienced many changes with the construction of toll roads and railroads. The variables for this study are land cover, built-up land and undeveloped land parameters. This study uses image interpretation analysis with Arcgis 10.3 and by doing a ground check to ensure the correctness of the interpretation. To test the accuracy of image interpretation is done with the overall accuracy confusion matrix with the kappa accuracy test results of 98.3% so that image interpretation can be trusted. This research is a qualitative research method with a descriptive approach. The results show that in a period of 10 years in Dibal Village there has been a decrease in productive agricultural land of around 9.69 hectares / 5.70%, while built-up land has increased by 9.69 hectares / 5.70%. The decrease in productive agricultural land consists of a decrease in rice fields and gardens. Productive agricultural land that has changed into built-up land includes rice fields and gardens that have turned into toll roads, railroads and community settlements.